Iodine Deficiency in a Study Population of Pregnant Women in Sweden. Issue 3 (September 2016) - Granfors, M.; Andersson, M.; Stinca, S.; Åkerud, H.; Skalkidou, A.; Sundström Poromaa, I.; Wikström, A.; Filipsson Nyström, H.
Abstract : ( Acta Obstet Gynecol Scand. 2015;94):1168–1174) Iodine requirements for women are approximately 50% greater in early pregnancy than when in the nonpregnant state. However, in Sweden, data on the iodine nutrition status of pregnant women are scarce and there are no current national recommendations concerning iodine supplementation during pregnancy. Therefore, in the present study, authors evaluated iodine nutrition in two cohorts of pregnant women in Sweden.